UZBEKISTAN- A LAND OF RICH CULTURAL HERITAGE - Teshaboyeva Nafisa Zubaydulla qizi; Rustamova Sarvinoz O’ktamjonovna (TADQIQOTLAR, 2025)
Abstract: Uzbekistan, located at the crossroads of ancient trade routes in Central Asia, possesses a diverse and multilayered cultural heritage shaped by centuries of historical development. This article examines the nation’s historical significance, emphasizing its prominent role along the Silk Road and analyzing its architectural masterpieces, including Samarkand’s Registan Square and the Historic Centre of Bukhara. It further explores Uzbekistan’s vibrant intangible cultural expressions— traditional craftsmanship, music, dance, oral storytelling, and cuisine—all of which continue to influence national identity. Additionally, the article considers modern initiatives dedicated to heritage preservation, such as restoration projects, educational programs, and sustainable tourism strategies. Ultimately, Uzbekistan’s commitment to safeguarding its cultural legacy ensures that its historical narrative remains relevant and appreciated worldwide.